2020
DOI: 10.1039/d0ra02763d
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous transport and magnetic properties induced by slight Cu valence alternation in layered oxytelluride BiCuTeO

Abstract: A nonlinear Hall effect and weak antiferromagnetism are induced by mixed-valence Cu in BiCuTeO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Among the layered oxychalcogenides, BiCuOX (X = S, Se, Te) was first identified by Kusainova et al [27]; it is composed of stacked (Bi 2 O 2 ) 2+ insulating layers and (Cu 2 X 2 ) 2− conducting layers. In the past 20 years, there have been many reports on a variety of novel and exciting properties of BiCuOX (X = S, Se, Te) phases, including magnetic properties [28][29][30], optical properties [31], transport properties [32,33] and thermoelectric (TE) properties [34,35]. For example, Karna et al reported the electrical and magnetic properties of slightly Cu-deficient BiCu 0.96 OSe using neutron and x-ray diffraction, AC magnetic susceptibility, magnetization and electric resistivity measurements [36].…”
Section: Introductionmentioning
confidence: 99%
“…Among the layered oxychalcogenides, BiCuOX (X = S, Se, Te) was first identified by Kusainova et al [27]; it is composed of stacked (Bi 2 O 2 ) 2+ insulating layers and (Cu 2 X 2 ) 2− conducting layers. In the past 20 years, there have been many reports on a variety of novel and exciting properties of BiCuOX (X = S, Se, Te) phases, including magnetic properties [28][29][30], optical properties [31], transport properties [32,33] and thermoelectric (TE) properties [34,35]. For example, Karna et al reported the electrical and magnetic properties of slightly Cu-deficient BiCu 0.96 OSe using neutron and x-ray diffraction, AC magnetic susceptibility, magnetization and electric resistivity measurements [36].…”
Section: Introductionmentioning
confidence: 99%